Concussions in athletics: Guidelines for return to sport - LeBlanc, K. E. (The Journal of the Louisiana State Medical Society, 1998)
Physicians are required to make determinations that affect the health and well-being of their patients on a daily basis. None of these judgments may have as profound an impact as the decisions rendered for athletes who have suffered a concussion. Concussions occur with regularity in sports and vary in severity and appropriate management. Guidelines should be followed and used as a tool to allow safe return to competitive endeavors in the athletic arena. Following guidelines will decrease the likelihood of worsening the condition with potentially fatal consequences. Concussions are not an uncommon event on the athletic playing field. They are sometimes thought of very lightly, as in the player who "had his bell rung". Less often, they are dealt with in dire situations, for example, "he has been unconscious for 12 hours". These two events represent extreme ends of the concussion spectrum. The initial management of each concussive event may be different. However, with inappropriate assessment and treatment, the seemingly inconsequential "ding" may result in permanent neurological deficits, while the unconscious athlete makes a complete recovery. Although there are no universally accepted standards in the evaluation and treatment of concussions, several authors have devised guidelines that may be employed in their management. Guidelines provide a framework that may be used in determining the grade and severity of the concussion. Additionally, these guidelines are helpful in deciding which athlete requires observation only or hospitalization and neuroimaging. The main focus of this article will be to familiarize the reader with the important aspects in dealing with the concussed athlete. Although several different guidelines have been proposed, a detailed discussion of all of them is beyond the scope of this paper. Rather, the more commonly used guidelines, as well as the management of concussions, will be discussed. Most importantly, the avoidance of post-concussive complications and the safe return to athletic competition will be stressed.